AcidoCEST-UTE MRI for the Assessment of Extracellular pH of Joint Tissues at 3 T. Issue 9 (September 2019) - Ma, Ya-Jun; High, Rachel A.; Tang, Qingbo; Wan, Lidi; Jerban, Saeed; Du, Jiang; Chang, Eric Y.
Abstract : Objectives: The goal of this study was to demonstrate feasibility of measuring extracellular pH in cartilage and meniscus using acidoCEST technique with a 3-dimensional ultrashort echo time readout (acidoCEST-UTE) magnetic resonance imaging (MRI). Materials and Methods: Magnetization transfer ratio asymmetry, radiofrequency (RF) power mismatch, and relative saturation transfer were evaluated in liquid phantoms for iopromide, iopamidol, and iohexol over a pH range of 6.2 to 7.8, at various agent concentrations, temperatures, and buffer concentrations. Tissue phantoms containing cartilage and meniscus were evaluated with the same considerations for iopamidol and iohexol. Phantoms were imaged with the acidoCEST-UTE MRI sequence at 3 T. Correlation coefficients and coefficients of variations were calculated. Paired Wilcoxon rank-sum tests were used to evaluate for statistically significant differences. Results: The RF power mismatch and relative saturation transfer analyses of liquid phantoms showed iopamidol and iohexol to be the most promising agents for this study. Both these agents appeared to be concentration independent and feasible for use with or without buffer and at physiologic temperature over a pH range of 6.2 to 7.8. Ultimately, RF power mismatch fitting of iohexol showed the strongest correlation coefficients between cartilage, meniscus, and fluid. In addition, ratiometric values for iohexol are similar among liquid as well as different tissue types. Conclusions: Measuring extracellular pH in cartilage and meniscus using acidoCEST-UTE MRI is feasible. Abstract : Supplemental digital content is available in the text.